2022
DOI: 10.3390/risks10010021
|View full text |Cite
|
Sign up to set email alerts
|

Non-Performing Loans and Macroeconomics Factors: The Italian Case

Abstract: The purpose of this work is to investigate the influence of macroeconomics determinants on non-performing loans (NPLs) in the Italian banking system over the period 2008Q3–2020Q4. We mainly contribute to the literature by being the first empirical article to study this relationship in the Italian context in the recent period, thus providing fresh evidence on the macroeconomic impact on NPLs, i.e., on the credit risk of Italian banks. By employing the Autoregressive Distributed Lag (ARDL) cointegration model, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 46 publications
3
28
2
1
Order By: Relevance
“…The macroeconomic variables in the study were found to have negative significant influence on NPLs. The findings indicated that higher GDP growth rate is more likely to decrease banks NPLs [18,15,27] and supports hypothesis 6. The study also found that higher inflation rate will result in less NPL which is contrary to the research hypothesis 7.…”
Section: Long Run Modelsupporting
confidence: 59%
See 1 more Smart Citation
“…The macroeconomic variables in the study were found to have negative significant influence on NPLs. The findings indicated that higher GDP growth rate is more likely to decrease banks NPLs [18,15,27] and supports hypothesis 6. The study also found that higher inflation rate will result in less NPL which is contrary to the research hypothesis 7.…”
Section: Long Run Modelsupporting
confidence: 59%
“…However, empirical evidence shows there exists a significant but a negative relationship between the growth in real GDP and NPLs in Ghana [18]. Again, Foglia [27], investigated the relationship between NPLs and the macroeconomic environment in the Italian context in the period 2008-2020. An ARDL cointegration model analysis performed, found GPD and Public Debt have a strong (negative) impact on the level of NPLs.…”
Section: Macroeconomic Factorsmentioning
confidence: 99%
“…The non-performing loans widely used in literature (Fofack, 2005;Antonin, 2018;Onomo, 2021;Foglia, 2022) draw the fact that banks extend credit to economic agents who do not return the credit on time. These adverse effects hold in credit allocation, in turn, harm the performance of the financial sector and the downside is that it increases price instability.…”
Section: Empirical Results and Analysismentioning
confidence: 99%
“…From 2008-2020, the cointegration and the distributed autoregressive lag model were used by Foglia (2022) to investigate the macroeconomic determinants of NPLs impact on the Italian banking system. Empirical findings show that the GDP prompted a negative influence on NPLs; On the contrary, the unemployment rate affected impaired loans positively [48].…”
Section: -2-empirical Findings On the Impact Of Macroeconomic Determi...mentioning
confidence: 96%